2020
DOI: 10.1186/s13063-020-04634-2
|View full text |Cite
|
Sign up to set email alerts
|

A quadruple blind, randomised controlled trial of gargling agents in reducing intraoral viral load among hospitalised COVID-19 patients: A structured summary of a study protocol for a randomised controlled trial

Abstract: Objectives 1- To compare the effectiveness of 1% Hydrogen peroxide, 0.2% Povidone-Iodine, 2% hypertonic saline and a novel solution Neem extract (Azardirachta indica) in reducing intra-oral viral load in COVID-19 positive patients. 2- To determine the salivary cytokine profiles of IL-2, IL-4, IL-6, IL-10, TNF-α, IFN-γ and IL- 17 among COVID-19 patients subjected to 1% Hydrogen peroxide, 0.2% Povidone-Iodine, 2% hypertonic saline or Neem extract (Azardirachta indica) based gargles. Trial design This will be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…64,65 Therapeutic agents administered through the upper airway have the potential to hamper SARS-CoV-2 evolution, especially in persistently infected individuals. Nasally administered povidone-iodine, 16 inhaled ciclesonide, 17 and hydrogen peroxide mouth rinses 20 are currently under investigation as antiviral/virucidal agents that may serve this purpose. Medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 Therapeutic agents administered through the upper airway have the potential to hamper SARS-CoV-2 evolution, especially in persistently infected individuals. Nasally administered povidone-iodine, 16 inhaled ciclesonide, 17 and hydrogen peroxide mouth rinses 20 are currently under investigation as antiviral/virucidal agents that may serve this purpose. Medicine.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Strategies to reduce viral replication at targeted anatomic sites will likely be effective in decreasing SARS-CoV-2 mortality and transmission because viral load correlates with disease severity and infectivity. [12][13][14] Additionally, several antiviral intranasal 15,16 , inhaled 17,18 , and oral rinse 19,20 formulations targeting the upper respiratory mucosa are currently under investigation and may become important measures to reduce COVID-19 disease burden/ transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Lim et al (2021) suggested A. indica as a potential herbal source of anti-SARS-CoV-2 agent with a multimodal efficacy of antiviral, anti-inflammatory, and immunomodulatory properties. Recently two different randomized controlled trials of A. indica extract/capsule on COVID-19 positive patients established the significant anti-SARS-CoV-2 potential in A. indica plant (Khan et al, 2020;Nesari et al, 2021). Similarly, few studies reported the Aloe vera phytochemicals as SARS-CoV-2 M pro and RdRp binding potential (Mpiana et al, 2020;Abouelela et al, 2021;Balkrishna et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A further example is Khan et al's clinical trial of gargling agents in reducing intraoral viral load among COVID-19 patients based in Pakistan [17]. is quadruple blind trial provides useful information because it is randomized and controlled, and one of their treatments is a 1% hydrogen peroxide gargle.…”
Section: Introductionmentioning
confidence: 99%